2018
DOI: 10.17796/1053-4628-42.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Localized Aggressive Periodontitis in Primary Dentition

Abstract: Objectives Due to the low prevalence of localized aggressive periodontitis (LAP), clinical characteristics of LAP in primary dentition are derived from a few case reports/series in the literature. The goal of this study was to determine common clinical characteristics such as bone and root resorption patterns, in a series of cases with LAP in primary dentition. We hypothesize these cases present aggressive periodontal bone destruction starting mostly around first primary molars and atypical root resorption pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
1
25
0
1
Order By: Relevance
“…Samples were collected as part of a larger clinical study approved by the University of Florida Institutional Review Board (IRB #201400349, ClinicalTrials.gov NCT01330719). The LAP patients had at least 2 sites with ≥5mm pocket depth and a history of site progression based on radiographic assessment, attachment loss of ≥3mm and bone loss on first molar or incisor and in no more than two teeth affected by bone loss other than first molar and incisor, and had not yet received any periodontal treatment in the previous 6 months, while periodontally healthy individuals presented with no pocket depth ≥5mm and absence of clinical attachment loss by full mouth probing and no evidence of bone loss by radiographic imaging [34,35]. Each plaque sample was collected from a first molar.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were collected as part of a larger clinical study approved by the University of Florida Institutional Review Board (IRB #201400349, ClinicalTrials.gov NCT01330719). The LAP patients had at least 2 sites with ≥5mm pocket depth and a history of site progression based on radiographic assessment, attachment loss of ≥3mm and bone loss on first molar or incisor and in no more than two teeth affected by bone loss other than first molar and incisor, and had not yet received any periodontal treatment in the previous 6 months, while periodontally healthy individuals presented with no pocket depth ≥5mm and absence of clinical attachment loss by full mouth probing and no evidence of bone loss by radiographic imaging [34,35]. Each plaque sample was collected from a first molar.…”
Section: Methodsmentioning
confidence: 99%
“…Other authors have suggested structural defects affecting these teeth as predisposing to LAgP, such as cementopathia/cemental hypoplasia or alterations in cementum formation and maturation . A recent study showed possible initiation on first primary molars of LAgP and abnormal root resorption patterns …”
Section: Introductionmentioning
confidence: 99%
“…Not all patients returned for an appointment at each timepoint, but all plaque samples collected at each timepoint were processed and analyzed. Reasons for missed appointments have been described previously; however, most were unknown, followed by forgetfulness, medical reasons, school activities or transportation issues [32]. Clinical parameters for all these sites at different timepoints are shown in Table 1.…”
Section: Resultsmentioning
confidence: 94%
“…Periapical and bite-wing x-rays were taken of the compromised teeth to confirm the C/MIP diagnosis. Examiners' calibration was obtained when 80% of duplicate measures of probing depth and CAL were within 1 mm [32].…”
Section: Clinical Measurementsmentioning
confidence: 99%